Peran Perbankan Syariah Dalam Meningkatkan Usaha Bagi Pengusaha Mikro di Kota Surakarta - Frichillia Elvira Agustina; Nabiil Afifah Putri Setiawan; Nadilla Nur Azizah; Fania Maulida Pangesti; Rita Wijayanti (Eqien - Jurnal Ekonomi dan Bisnis, 2023)
One of the roles of Islamic banks in developing the economy of a country including Indonesia is very large, almost all sectors related to financial activities will require various banking services. Therefore, we really need the banking world now and in the future, both companies and individuals. Related to banking functions, namely as a financial institution that collects and distributes public funds and facilitates trade transactions. Small and Medium Enterprises (MSMEs) which is one of the forces that can drive economic growth. MSMEs are currently developing very rapidly so that Islamic banking has the opportunity to grow the economy of a region. The existence of Bank BSI (Btpn Syariah) KCP Surakarta provides results and impacts for micro and medium enterprises. This can be seen from the improved customer business after financing at Bank BSI (BTPN Syariah) KCP Surakarta. In addition, customers also experienced an increase in revenue, increased sales volume, and the addition of new employees to their business after financing Bank BSI (BTPN Syariah) KCP Surakarta. Data analysis techniques begin by examining all available data from various sources, namely from interviews, observations that have been written in field notes, personal documents